Exploring thematic unity and stylistic diversity in multi-film scoring practices: the case of hedwig’s theme. - Zoio, Katya Izabella (Stellenbosch : Stellenbosch University, 2022)
Thesis (MMus)--Stellenbosch University, 2023.